PENGARUH KUALITAS PRODUK DAN STORE ATMOSPHERE TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA JEBER CAFE PLATINUM DI KOTA PEKANBARU - Ulfa, Monica; Zulkarnain, Zulkarnain; Henni, Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to discuss the Effect of Product Quality on CustomerSatisfaction and Loyalty at Jeber Platinum Cafe in Pekanbaru City. Thepopulation in this study included all customers who had visited Jeber CafePlatinum whose numbers were not known with certainty. The sample used in thisstudy is 100 customers and has a minimum 2x visit criteria. Primary data iscollected by questionnaire as an instrument to prove the results of the study, totest the hypothesis in this study is to use path analysis. The results showed thatproduct quality has a positive effect with a strong level of influence on customersatisfaction, store atmosphere has a positive effect with a strong level of influenceon customer satisfaction, store atmosphere has a positive effect on the level ofinfluence that customer satisfaction has a positive influence on a strong level ofcustomer loyalty, product quality has a positive effect on the level of customerloyalty through customer satisfaction, store atmosphere has a positive effect onthe level of customer loyalty through satisfaction customer. The better the qualityof the product provided, the satisfaction will increase, the better the storeatmosphere is given, the satisfaction will increase, the stronger customersatisfaction will be obtained, the customer loyalty will increase. The better thequality of the product provided, the customer satisfaction through loyalty willincrease, the better the store atmosphere is given, the greater customersatisfaction through loyalty.Keywords: Product quality, store atmosphere, customer satisfaction, customerloyalty